2003
DOI: 10.1596/1813-9450-2988
|View full text |Cite
|
Sign up to set email alerts
|

Trade Facilitation and Economic Development: Measuring the Impact

Abstract: This paper analyzes the relationship between trade facilitation, trade flows, and GDP per capita in the Asia-Pacific region for the manufacturing sector. The paper first defines and measures trade facilitation using four broad indicators: port efficiency, customs environment, regulatory environment, and e-business usage. Using a gravity model, we estimate that enhanced port efficiency and customs environment have a positive effect on bilateral trade. Based on a scenario in which APEC members below average impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 12 publications
5
80
0
10
Order By: Relevance
“…Wilson, Mann, and Otsuki (2005), when extending the gravity model to trade facilitation measures and to a larger sample of 75 economies, posited that port efficiency and the proxies for infrastructure quality for the services sector, such as the use, speed, and cost of the internet, significantly affected trade flows. Wilson, Mann, and Otsuki (2003) also found that that improving port and airport efficiency could positively impact intra-APEC trade. Bougheas, Demetriades, and Morgenroth (1999), in developing a gravity model to analyze the effect of infrastructure on the volume of trade via its influence on transport costs, found that infrastructure had a significant and positive relationship to the level of infrastructure and the volume of trade.…”
Section: Infrastructure Development In Asiamentioning
confidence: 92%
“…Wilson, Mann, and Otsuki (2005), when extending the gravity model to trade facilitation measures and to a larger sample of 75 economies, posited that port efficiency and the proxies for infrastructure quality for the services sector, such as the use, speed, and cost of the internet, significantly affected trade flows. Wilson, Mann, and Otsuki (2003) also found that that improving port and airport efficiency could positively impact intra-APEC trade. Bougheas, Demetriades, and Morgenroth (1999), in developing a gravity model to analyze the effect of infrastructure on the volume of trade via its influence on transport costs, found that infrastructure had a significant and positive relationship to the level of infrastructure and the volume of trade.…”
Section: Infrastructure Development In Asiamentioning
confidence: 92%
“…Entretanto, esses autores não encontraram instrumentos para corrigir tal problema. Wilson et al (2003) não se depararam com significativo viés de endogeneidade dessa variável em suas estimativas de equações de gravidade para a Cooperação Econômica Ásia-Pacífico (APEC).…”
Section: Modelo Empíricounclassified
“…Wilson et al (2003), for instance, analyse the relationship between trade facilitation, trade flows and economic development in the Asia-Pacific region for the goods sector. Four indicators of trade facilitation are used: port efficiency (to capture the quality of infrastructure of maritime and air ports), customs environment, regulatory environment and electronic-business usage.…”
Section: I T E R a T U Re R Ev I Ewmentioning
confidence: 99%